2020
DOI: 10.1051/0004-6361/201936111
|View full text |Cite
|
Sign up to set email alerts
|

Galactic cirri in deep optical imaging

Abstract: The ubiquitous presence of Galactic cirri in deep optical images represents a major obstacle to study the low surface brightness features of extragalactic sources. To address this issue, we have explored the optical properties of cirri using g, r, i, and z bands in the Sloan Digital Sky Survey (SDSS) Stripe82 region. Using state-of-the-art, custom made, image processing techniques, including the modeling and removal of the instrumental scattered light produced by the stars, we managed to isolate the optical di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
116
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 86 publications
(136 citation statements)
references
References 105 publications
13
116
0
Order By: Relevance
“…The depth of the data in the environment of NGC 1052 is remarkable, however we found that it is not homogeneous, varying from 29.2 to 29.9 mag arcsec −2 in the g band, from 28.7 to 29.1 mag arcsec −2 in the r band, and from 27.5 to 27.6 mag arcsec −2 in the z band, all measured as 3σ in 10×10 arcsec boxes following the depth definition by Román et al (2020), Appendix A. This range in depth is from approximately 0.5 to 1 mag arcsec −2 deeper than the typical depth of the DECaLS data in other regions (see Martinez-Delgado et al 2021b).…”
Section: Datamentioning
confidence: 73%
See 1 more Smart Citation
“…The depth of the data in the environment of NGC 1052 is remarkable, however we found that it is not homogeneous, varying from 29.2 to 29.9 mag arcsec −2 in the g band, from 28.7 to 29.1 mag arcsec −2 in the r band, and from 27.5 to 27.6 mag arcsec −2 in the z band, all measured as 3σ in 10×10 arcsec boxes following the depth definition by Román et al (2020), Appendix A. This range in depth is from approximately 0.5 to 1 mag arcsec −2 deeper than the typical depth of the DECaLS data in other regions (see Martinez-Delgado et al 2021b).…”
Section: Datamentioning
confidence: 73%
“…Given the large radius expected for the LSBGs in our sample, there is a wide margin to carry out this loss-of-resolution process by rebinning the pixel scale. This method of enhancing the diffuse emission by averaging small spatial scales has been used in previous works with good results (Zaritsky et al 2019;Román et al 2020). The operation of this pipeline is the following: We create a deep g + r image that is going to be used as a detection image.…”
Section: Detection Of Low-surface-brightness Galaxiesmentioning
confidence: 99%
“…The co-addition of frames was performed using a pipeline with a resistant median-based combination algorithm, efficiently rejecting satellite tails, cosmic rays and other artefacts. The depth of the final coadded image is 28.4 mag arcsec −2 (3 sigma in a 10x10 box) following the definition provided in appendix A of Román et al (2020).…”
Section: Data Acquisitionmentioning
confidence: 99%
“…For this, we carried out specific observations of bright stars to produce a high signal-to-noise large-radius point spread function (PSF) model. We follow a processing similar to that carried out by Román et al (2020) and Infante-Sainz, Trujillo & Román (2020). Given the excellent circular symmetry of the PSF of this telescope, we constructed a PSF model averaging the flux in the azimuthal direction, hence maximizing the signal-to-noise of the model.…”
Section: T R Ac I N G T H E S T E L L a R S T R E A M I N T H E I N N E R H A L O O F M 1 0mentioning
confidence: 99%
“…Given the excellent circular symmetry of the PSF of this telescope, we constructed a PSF model averaging the flux in the azimuthal direction, hence maximizing the signal-to-noise of the model. Finally we run the scattered-light modelling pipeline developed by Román et al (2020) producing the model of the light scattered by the stars in the field (see Fig. 4).…”
Section: T R Ac I N G T H E S T E L L a R S T R E A M I N T H E I N N E R H A L O O F M 1 0mentioning
confidence: 99%